Ethnic Identity in Emerging Adults in Sub‐Saharan Africa and the USA, and Its Associations with Psychological Well‐Being. (17th September 2015) - Adams, Byron G.; Abubakar, Amina; Van de Vijver, Fons J. R.; De Bruin, Gideon P.; Arasa, Josephine; Fomba, Emmanuel; Gillath, Omri; Hapunda, Given; Looh La, Joseph; Mazrui, Lubna; Murugami, Margaret
Abstract: Ethnic identity as a social dimension of identity is argued to be developmentally important for psychological well‐being. However, the relationships between these constructs are mainly examined in Western contexts, amongst dominant–non‐dominant groups. We investigate ethnic identity across the mainstream group of a prototypical Western society (the USA) and several multi‐ethnic sub‐Saharan African countries (Cameroon, Kenya, South Africa, and Zambia), as well as how it relates to psychological well‐being. A total of 1255 university students (61.8% females, M age = 20.94 years, SD = 2.97) completed a questionnaire with ethnic identity and psychological well‐being measures. Results indicated that ethnic identity was most salient in two different South African ethnocultural samples and least salient in a mainstream US sample. These results suggest that groups that are more exposed to ethnic strain in multicultural societies tend to have more salient ethnic identities. Furthermore, the underlying structure in the ethnic identity psychological well‐being relationship was similar across groups. Copyright © 2015 John Wiley & Sons, Ltd.